Quantitative Clinical Cardiac Magnetic Resonance Imaging - Reiter, Ursula; Reiter, Clemens; Kräuter, Corina; Nizhnikava, Volha; Fuchsjäger, Michael H.; Reiter, Gert (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background Cardiac magnetic resonance imaging (MRI) represents the established reference standard method for the assessment of cardiac function and non-invasive evaluation of myocardial tissue in a variety of clinical questions, wherein quantification of cardiac parameters gains growing diagnostic and differential-diagnostic importance. This review aims to summarize established and newly emerging quantitative parameters, which are assessed in routine cardiac MRI. Interrelations and interdependencies between metrics are explained, and common factors affecting quantitative results are discussed.Method The review is based on a PubMed literature research using the search terms “cardiac magnetic resonance” and “quantification”, “recommendations”, “quantitative evaluation/assessment”, “reference method”, “reference/normal values”, “pitfalls” or “artifacts” published between 2000–2019.Results and Conclusion Quantitative functional, phase contrast, and perfusion imaging, as well as relaxation time mapping techniques give opportunity for assessment of a large number of quantitative cardiac MRI parameters in clinical routine. Application of these techniques allows for characterization of function, morphology and perfusion of the heart beyond visual analysis of images, either in primary evaluation and comparison to normal values or in patients’ follow-up and treatment monitoring. However, with implementation of quantitative parameters in clinical routine, standardization is of particular importance as different acquisition and evaluation strategies and algorithms may substantially influence results, though not always immediately apparent.Key Points: Citation FormatHintergrund Die kardiale Magnetresonanztomografie (MRT) stellt sowohl in der Beurteilung der Herzfunktion als auch zur nichtinvasiven Gewebsanalyse des Myokards in vielen klinischen Fragestellungen die Referenz-Standard-Methode dar. Speziell die Quantifizierung kardialer Parameter nimmt eine immer zentralere diagnostische und differenzialdiagnostische Rolle ein. Im vorliegenden Review sollen etablierte und vielversprechende neue quantitative Herz-MRT-Parameter der klinischen Routine zusammengefasst, ihre Zusammenhänge beschrieben sowie ihre Abhängigkeiten von substanziellen Einflussfaktoren dargestellt werden.Methode Die Übersichtsarbeit basiert auf einer PubMed-Literaturrecherche zu den Begriffen „cardiac magnetic resonance“ und „quantification“, „recommendations“, „quantitative evaluation/assessment“, „reference method“, „reference/normal values“, „pitfalls“ sowie „artifacts“ innerhalb des Publikationszeitraums 2000–2019.Ergebnisse und Schlussfolgerung Funktionelle, Phasenkontrast- und Perfusionsbildgebung sowie Relaxationszeit-Kartierung ermöglichen die Erfassung einer Vielzahl quantitativer Herz-MRT-Parameter. Diese erlauben eine über die visuelle Beurteilung von Herz-MRT-Bildern hinausgehende Charakterisierung der Funktion, Morphologie und Perfusion des Herzens, sei es im Vergleich zu Normalwerten oder im Therapieverlauf. Bei der Interpretation ausgewerteter Herz-MRT-Parameter in der klinischen Routine muss allerdings zunehmend auf Standardisierung geachtet werden, da Aufnahmetechniken und Auswertealgorithmen quantitative Ergebnisse maßgeblich – jedoch mitunter nicht unmittelbar erkennbar – beeinflussen können.Kernaussagen: Zitierweise
Keywords: heart; MR-imaging; cardiac function; myocardial relaxation time mapping; myocardial perfusion; pitfalls